The distributional effects of value added tax in Ireland - Eimear Leahy; Seán Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
In this paper we examine the distributional effects of Value Added Tax (VAT) in Ireland. Using the 2004/2005 Household Budget Survey, we assess the amount of VAT that households pay as a proportion of weekly disposable income. We measure VAT payments by equivalised income decile, households of different composition and different household sizes. The current system is highly regressive. With the use of a micro-simulation model we also estimate the impact of changing the VAT rate on certain groups of items and the associated change in revenue. We also consider how the imposition of a flat rate across all goods and services would affect households in different categories. The Irish Government has recently announced that it proposes to increase the standard rate of VAT to 22% in 2013 and to 23% in 2014. We examine the distributional implications of such increases. The general pattern of results shows that those hardest hit are households in the first income decile, households in rural areas, 6 person households and households containing a single adult with children.
Keywords: 330